Systematic Literature Review: Integrating Islamic Education in English Language Teaching - Djamdjuri, Dewi Suriyani; Thoyib, Mastur; Supriadi, Dedi; Handayani, Ika; Furqan, Muhammad; Nurmuntazlimah, Keisha Siti (Universitas Muhammadiyah Malang, 2023)
The process of learning English in Indonesia is structured in such a way as to enable students to master the ability to listen, speak, read and write the language. Unfortunately, this language learning method is not compatible with religious learning methods. The following discussion will further explain the objectives of this research which examines Islamic Education in English Teaching. The keywords used to find articles in the database are “Islamic Education in English Teaching”. The search results found 50 publications, then 12 manuscripts were selected that met the criteria for analysis. The reporting items selected for systematic literature reviews and meta-analyses are inclusion and exclusion models. In the last three years, the number of publications was dominated by 2020 with a total of 5 articles published. The research subjects used by the researchers consisted of 3rd grade elementary school students, 7th grade elementary school students, 8th grade junior high school students, a combination of middle school and high school students, 11th grade high school students, and university students. There are 12 research contributions that can be reflected in the English language learning process which is integrated with Islamic values.